Analysis of logistics service supply chain for the One Belt and One Road initiative of China. (September 2018) - Liu, Xiaotong; Zhang, Kai; Chen, Bokui; Zhou, Jun; Miao, Lixin
Highlights: This work addresses the coordination issues of logistics service supply chain induced by OBOR. Mass customization service mode and cost-sharing contract are considered. Four gaming models of cost-sharing contract are proposed. The impact of cost-sharing proportion on performance and key decisions of supply chain are provided. Abstract: This paper explored the supply chain coordination issues arising from the One Belt and One Road initiative (OBOR), and investigated the impacts of the cost sharing contract on the key decisions for logistics service supply chain with mass customization. Our motivation was derived from the growing individualized demands for logistics service in the OBOR region. In this study, a logistics services supply chain, consisting of one functional logistic service provider (FLSP) and one logistics service integrator (LSI), was considered and performed on the OBOR. Based on a game theoretic approach, the supply chain performance was evaluated with four models of the cost sharing contract between the FLSP and the LSI, respectively. As a result, several key managerial insights were discovered in our modeling study. More importantly, the impacts of cost-sharing on the key decisions of each player was analyzed in details, and the interaction mechanism of mass customization was also estimated. From our perspective, it will be indeed beneficial to improving logistics service in the OBOR region.